The Reflections of Lean Digitalization in Indian MSMEs: A Case Study - Singh, Hirendra; Singh, Bhim (International Journal of Membrane Science and Technology, 2023)
Lean production is very widely used and thoroughly tested approach among various enterprises for many decades, its motive is to remove non-value-added activities (waste) from the value stream and make the system highly optimized and efficient. Industry 4.0 is combination of technology driven applications that merge the traditional physical industry to cyber word with the use of digital technology, IoT and sensors etc. In today’s highly competitive and volatile market scenarios it is very hard to fulfill the consumer demands and to produce highly customized quality product, without applications of integrated lean principles and industry 4.0 technologies. This combination known as lean 4.0, is not a replacement for either Industry 4.0 or Lean, but rather a way to improve the performance of the industrial sector. This study looks at how lean manufacturing principles can be used with Industry 4.0 to help India's hard-hit Micro, Small, and Medium-Enterprises (MSMEs). The concepts of lean 4.0 were tested in selected Micro, Small, and Medium-Sized Enterprises at the NCR region in India. Different parameters of productivity and customer satisfaction index has been compared after traditional lean and lean 4.0 implementation, there is a significant improvement has been observed as a result, another aim of this study is to put effort to persuade MSMEs to accept this fusion in order to boost productivity, quality and customer satisfaction.